2021
DOI: 10.15678/eber.2021.090101
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of economic sentiment and GDP growth in Russia in light of the Covid-19 crisis

Abstract: The objective of the article is to prove the empirical and predictive value of the aggregate opinions of businesses and households for expanding cyclical macroeconomic data in Russia, especially during the coronavirus shocks. Research Design & Methods: We use qualitative information from surveys that cover about 24 000 organisations and 5100 households in all Russian regions. The total economic sentiment indicator (TESI) combines information on 18 survey-based indicators. Cross-correlation analysis, Hodrick-Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…This would show the actual effectiveness of energy policy and orientate towards building competitive advantage of countries based on clean technologies. The Covid-19 pandemic impacted many aspects of social and economic life [76][77][78][79][80], included the energy policy. Until the Covid-19 pandemic outbreak, industrial emissions had the highest decrease, but aviation emissions had increased [57].…”
Section: Suggestions For Further Studiesmentioning
confidence: 99%
“…This would show the actual effectiveness of energy policy and orientate towards building competitive advantage of countries based on clean technologies. The Covid-19 pandemic impacted many aspects of social and economic life [76][77][78][79][80], included the energy policy. Until the Covid-19 pandemic outbreak, industrial emissions had the highest decrease, but aviation emissions had increased [57].…”
Section: Suggestions For Further Studiesmentioning
confidence: 99%
“…Recently, the spectre of the Covid-19 pandemic has been looming over the global economy (Lipkind & Kitrar, 2021;Żak & Garncarz, 2020). This pandemic not only results in serious impacts on the communities in the influenced regions, but it also leads to various levels of negative and profound mental health issues to both infected and uninfected people (Feng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The case study also showed that confidence indicators can be useful for predicting the rate of economic growth of real GDP in the short run in most of the observed countries. In 2021, predictive value was demonstrated for GDP dynamics based on consumer and business perceptions, and a correlation was found based on economic shocks caused by the COVID-19 pandemic (Kitrar, 2021). The same study also points out that consumer and business assessments are reliable and available long before quantitative GDP growth statistics and can be used as an early warning system of economic growth dynamics and taken into account in policy making.…”
Section: Literature Reviewmentioning
confidence: 90%